Infection of B Cell Follicle-Resident Cells by Friend Retrovirus Occurs during Acute Infection and Is Maintained during Viral Persistence - Sonja Windmann (American Society for Microbiology, 2019)
ABSTRACT B cell follicles of the spleen and lymph nodes are immune privileged sites and serve as sanctuaries for infected CD4+ cells in HIV infection. It is assumed that CD8+ T cell responses promote the establishment of the reservoir, as B cell follicles do not permit CD8+ T cell entry. Here we analyzed the infected cell population in the Friend retrovirus (FV) infection and investigated whether FV can similarly infect follicular cells. For analysis of FV-infected cells, we constructed a recombinant FV encoding the bright fluorescent protein mWasabi and performed flow cytometry with cells isolated from spleens, lymph nodes and bone marrow of FV-mWasabi-infected mice. Using t-stochastic neighbor embedding for data exploration, we demonstrate how the target cell population changes during the course of infection. While FV was widely distributed in erythrocytes, myeloid cells, B cells, and CD4+ T cells in the acute phase of infection, the bulk viral load in the late phase was carried by macrophages and follicular B and CD4+ T cells, suggesting that FV persists in cells that are protected from CD8+ T cell killing. Importantly, seeding into follicular cells was equally observed in CD8+ T cell-depleted mice and in highly FV-susceptible mice that mount a very weak immune response, demonstrating that infection of follicular cells is not driven by immune pressure. Our data demonstrate that infection of cells in the B cell follicle is a characteristic of the FV infection, making this murine retrovirus an even more valuable model for development of retrovirus immunotherapy approaches. IMPORTANCE Human immunodeficiency virus is notorious for its ability to avoid clearance by therapeutic interventions, which is partly attributed to the establishment of reservoirs in latently infected cells and cells that reside in immunologically privileged B cell follicles. In the work presented here, we show that cells of the B cell follicle are equally infected by a simple mouse gammaretrovirus. Using fluorescently labeled Friend retrovirus, we found that B cells and T cells in the B cell follicle, while not carrying the bulk of the virus load, were indeed infected by Friend virus in the early acute phase of the infection and persisted in the chronic infection. Our results suggest that infection of follicular cells may be a shared property of lymphotropic viruses and propose the FV infection of mice as a useful model to study strategies for follicular reservoir elimination.